Dynamics Linkages among Money, Output, Interest Rate and Price: The Case in Malaysia - Ooi, Ai-Yee; Brahmana, Rayenda Khresna (Canadian Center of Science and Education, 2011)
This paper aims to examine the factors of monetary policy transmission that affecting output and inflation variability in Malaysia. By using quarterly data from 1980 to 2008, the results suggest that money is a lead output indicator and is also essential to curb inflation and maintain high growth rate in GDP. Interest rate is found as another important intermediate target in the monetary policy transmission mechanism in affecting output variability. The absence of causality from real GDP to price suggests that the excess of aggregates demand generated by increase in real GDP is absorbed by growth in aggregate supply.